Corporate financing decisions when investors take the path of least resistance - Baker, Malcolm; Coval, Joshua; Stein, Jeremy C. 1960- (National Bureau of Economic Research, 2004)
"We explore the consequences for corporate financial policy that arise when investors exhibit inertial behavior. One implication of investor inertia is that, all else equal, a firm pursuing a strategy of equity-financed growth will prefer a stock-for-stock merger to greenfield investment financed with an SEO. With a merger, acquirer stock is placed in the hands of investors, who, because of inertia, do not resell it all on the open market. If there is downward-sloping demand for acquirer shares, this leads to less price pressure than an SEO, and cheaper equity financing as a result. We develop a simple model to illustrate this idea, and present supporting empirical evidence. Both individual and institutional investors tend to hang on to shares granted them in mergers, with this tendency being much stronger for individuals. Consistent with the model and with this cross-sectional pattern in inertia, acquirers targeting firms with high institutional ownership experience more negative announcement effects and greater announcement volume. Moreover, the results are strongest when the overlap in target and acquirer institutional ownership is low and when the demand curve for the acquirer's shares appears to be steep"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Corporations -- Finance -- Econometric models